1991
DOI: 10.1080/00420989120080431
|View full text |Cite
|
Sign up to set email alerts
|

On Resolving the Dilemma of Rent Control

Abstract: This research examines the motivations for adopting rent control and discusses a policy alternative designed to respond to the political appeal of rent control while minimising the investment distortion, capricious redistribution and administrative complexity of most controls . The policy involves limiting regulation to those rents paid by households in the tenant population that are deemed unable to afford adequate housing. All rental units in a jurisdiction register their rents with the relevant authority an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An Ontario Economic Council study (Arnott, 1981) recommended a gradual phasing-out of rent control to no avail, while a Royal Commission's fouryear study was similarly ignored . Among others, the works contributing to this understanding include Olsen (1969) ; Olsen (1972); Cheung (1975) ; Frankena (1975) ; Arnott (1981) ; Marks (1984aMarks ( , 1984b ; Fallis and Smith (1984) ; Gyourko and Linneman (1990) ; Albon and Stafford (1990) ; Miron (1990) ; Marks (1991) . 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An Ontario Economic Council study (Arnott, 1981) recommended a gradual phasing-out of rent control to no avail, while a Royal Commission's fouryear study was similarly ignored . Among others, the works contributing to this understanding include Olsen (1969) ; Olsen (1972); Cheung (1975) ; Frankena (1975) ; Arnott (1981) ; Marks (1984aMarks ( , 1984b ; Fallis and Smith (1984) ; Gyourko and Linneman (1990) ; Albon and Stafford (1990) ; Miron (1990) ; Marks (1991) . 2 .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation to this 'unstable market hypothesis', offered by Marks (1991), is based on political economy considerations . Sitting tenants, according to Marks, have a great deal of political influence because, unlike landlords whose votes are believed to go to business-oriented candidates anyway, they are likely to be `marginal voters' whose votes depend crucially on candidates' support for rent control .…”
Section: The Rationale Behind Rent Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies on rent control utilize economic models based on computer simulations of case studies. Literature that utilizes economic modeling has concluded that rent control lowers rents (Hubert, 1993;Lewis & Muller, 1992;Albon & Stafford, 1990;Marks, 1991). Other studies that have used economic modeling have found reductions in maintenance (Ho, 1992) and increases in the rent of undesirable tenants (Miron, 1990) under rent control ordinances.…”
Section: Previous Researchmentioning
confidence: 99%